Quadrotor Unmanned Aerial Vehicle-Mounted Launch Device Precision Analysis for Countering Intruding Drones - Yanan He; Lingsong Di; Huiqi Xu; Weigui Zeng; Wei Li; Silei Cao (Drones)
In light of the current issue of commercial and modified drones frequently intruding into sensitive locations such as airports, this paper proposes the use of quadrotor drones equipped with a launch device for interception. For an “X”-shaped quadrotor drone equipped with a two-degree-of-freedom gimbal launch device, dynamic, control, and ballistic models are constructed to analyze the impact of single-shot firing on the drone’s attitude and the factors affecting accuracy in rapid-fire scenarios. Simulation results indicate that downward firing has the highest shooting accuracy and is suitable for counter-drone missions. For single-shot firing, lateral downward firing compared to frontal firing can effectively reduce attitude and position changes, which is beneficial for engaging stationary targets. In the case of rapid fire, control of the firing interval is crucial for accuracy; a larger firing interval can significantly enhance shooting precision. When firing small payloads in rapid succession, vertical downward firing has the highest accuracy, while lateral firing results in a larger distribution radius of the impact points. To improve shooting accuracy, frontal firing is recommended. Future research will further explore the dynamic response of drones under different firing conditions and develop more advanced control strategies to enhance their practical performance and reliability.